Transport of uncharged organic solutes in Xenopus oocytes expressing red cell anion exchangers (AE1s) - Fiévet, Bruno (The National Academy of Sciences, 1998)
When expressed in Xenopus oocytes, the trout red cell anion exchanger tAE1, but not the mouse exchanger mAE1, elicited a transport of electroneutral solutes (sorbitol, urea) in addition to the expected anion exchange activity. Chimeras constructed from mAE1 and tAE1 allowed us to identify the tAE1 domains involved in the induction of these transports. Expression of tAE1 (but not mAE1) is known to generate an anion conductance associated with a taurine transport. The present data provide evidence that (i) the capacity of tAE1 and tAE1 chimeras to generate urea and sorbitol permeability also was associated with an anion conductance; (ii) the same inhibitors affected both the permeability of solutes and anion conductance; and (iii) no measurable water transport was associated with the tAE1-dependent conductance. These results support the view that fish red blood cells, to achieve cell volume regulation in response to hypotonic swelling, activate a tAE1-associated anion channel that can mediate the passive transport of taurine and electroneutral solutes.